Extracurricular factors influence perceived stress in a large cohort of Colombian dental students (2023)
The aim of this study was to investigate the association of extracurricular factors including socioeconomic status and career choice with perceived stress in dental school in a large cohort of Colombian dental students. Participants in the study were 5,700 students enrolled in seventeen Colombian dental schools. The study employed a Spanish adaptation of the Dental Environment Stressors (DES30-Sp) questionnaire and recorded an array of demographic, socioeconomic, career choice, and dental studies-related information. Data analyses relied on descriptive, bivariate, and multivariate methods based on multi-level mixed-effects linear regression and post hoc estimation of predictive margins. "Fear of failing a course or year" emerged as the highest ranked item. Male students consistently reported less perceived stress than females, and stress scores were higher among seniors. Independent of gender, age, and study year, having dentistry as one's first career choice, relying on financial support, and belonging to higher socioeconomic strata were associated with lower stress levels. Academic environment interventions aimed to improve students' educational well-being will need to account for the individual heterogeneity among them. These data from a robust cohort of predoctoral dental students underscore the importance of considering students' educational experiences in a broader social and economic context.